The significance of a pre-service RE course, which recognises the importance of a focus on the inner life : exploring the experience of primary teacher education students in a small teacher education college in Dublin - O'Connell, John Gerard (University of Exeter, 2014)
This thesis reports the findings of a research study conducted in an initial primary teacher education college in Dublin, exploring how teacher education students experienced and constructed meaning from a pre-service RE course which recognized the importance of a focus on their inner lives. The study, which adopted a qualitative interpretive approach, was conducted using semi-structured interviews with twelve past students from a recently-graduated year group of one hundred students. The study hoped to uncover how a focus on the inner life was taken up by the research participants in relation to their personal and professional wellbeing and their role as educators in general and religious educators in particular. While it did not seek to generalise as a result of the findings, confined as it is by time and circumstance, nevertheless aspects deemed worthwhile by the research participants may also be deemed worthwhile by the reader and indeed may not be confined to the domain of RE. The findings have been framed generally against the three themes of ‘particularity’, ‘inner-ness’ and ‘ongoing-ness’. The theme of ‘particularity’ relates to the participants’ epistemological journey, as it is concerned with how concrete elements of the course supported inner life work. The theme of ‘inner-ness’ relates to the participants’ ontological journey, as it is concerned with how participants experienced and made meaning from the space provided by the course for inner life work. The theme of ‘ongoingness’ relates to the total RE journey from primary and secondary school to college and into their teaching lives and its impact on participants’ inner lives. What is clear from participants’ responses is that the RE course, and particularly the elements of the RE course that had a focus on the inner life, had a significant impact on participants’ identity, both personal and professional, at an important stage of their development and personal story. The study demonstrates the importance of inner life work for teacher education students and contributes a level of insight into how students appropriate and construct meaning from a created and creative space that supports a focus on that inner life.
Educational Doctorate
Keywords: initial teacher education; Religion; spirituality; qualitative